Formation and Development of Lexemes in the Field of Trade (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Language and trade have been closely linked throughout history, influencing and shaping each other as trade expanded across regions and cultures. The study of trade-related words as a linguistic category reveals not only the mechanisms of word formation and acquisition, but also socio-economic and historical factors that cause lexical changes. In this context, etymological studies play a crucial role in understanding how commercial lexemes appear, develop and adapt in languages.This article makes a comparative analysis of the words used in trade in the Uzbek and English languages, focusing on their linguistic origin, word formation processes, and semantic evolution. While English has historically incorporated business vocabulary from Latin, French, and Dutch, Uzbek has been influenced by Persian, Arabic, Russian, and, in recent years, English. The study examines how these influences have shaped the commercial lexicon in both languages, taking into account phonetic, morphological and semantic adaptations.